Tools for evaluating science in universities and R&D centres: descriptions and usage - Torres-Salinas, Daniel; Cabezas-Clavijo, Álvaro (Anuario ThinkEPI, 2012)
Indicators have become essential to Spanish universities. Some of the major funding calls for proposals (Campus of international excellence, Severo Ochoa centres of excellence, etc.) rely heavily on R&D indicators. We review some of the tools that universities have to generate indicators, apart from the traditional citation indexes: 1) scientific information systems, 2) bibliometric suites from commercial companies, and 3) university rankings. The use of these tools and the need for librarians to manage them are discussed.
Keywords: Bibliometric indicators; Scientific information systems; Rankings of universities; Research management.